Social aspect of the journey of hydrogen as an energy source and a alternative fuel in Singapore - Wong, Ao Shen (Nanyang Technological University, 2023)
With the goal of net-zero emissions by 2050, it is inevitable for Singapore to undergo an energy transition, and Singapore is looking into the potential of hydrogen as a clean energy source to decrease her dependence on fossil fuels. While competition is rising globally, there are technical challenges that Singapore may face during the adoption of hydrogen. This report investigates the social aspects of integration and implementation of hydrogen as a main source of energy in Singapore, which encompasses all related social impacts down the hydrogen supply chain. The literature review investigated past studies from countries such as Germany, Japan, Spain, and Australia, all with social perception and acceptance as their main scopes. The studies found the effects of different social and cultural factors, such as risk perception and levels of environmental awareness, on the support and acceptance of hydrogen in those regions. Each region slightly differed in the impacts of said factors. This study investigated the main gaps in introducing any new source of energy to a society, which is the question of whether society is ready for the implementation of this alternative fuel, and what Singapore can do to minimise the negative social impacts and the effects of implementation. A mass multiple-choice question (MCQ) survey targeted to the Singaporean public, and some casual interviews revealed high levels of support for hydrogen, but lower levels of knowledge on the subject. A large generation gap was also revealed between generation X and the younger groups, which highlighted the importance of sustainable childhood habits, long-term educational campaigns, and exposure to information on trusted informational sources. Furthermore, safety perception of hydrogen plays a significant role in determining overall support and acceptance of commercialised hydrogen technologies for use in public settings, which further pushed for the importance of education of hydrogen. It can be concluded that while support is positive, the society at a whole may not be ready for this transition now due to insufficiently high support and acceptance levels. Through the findings, there are still opportunities for Singapore to do better and improve public perception of hydrogen. These opportunities are addressed through 4 recommendations, addressing 4 social factors directly impacting support levels, which can be summarised as educational campaigns, publicised pilot tests, targeted information dissemination, and fostering of good childhood habits. These recommendations hope to set up an accepting and supportive social environment for a smooth green energy transition in Singapore.